Prediction Model for Low Birth Weight (LBW) in East Lombok Regency - Nurlaili, Mustika; Masyhurrosyidi, Hadi; Sastrawan, Sastrawan; Sulaiman, Lalu (Adult Health Nursing Journal, 2025)
Introduction: The success of midwifery care has an impact on maternal health and greatly influences future generations of the nation and state. Purpose: recommendations for reducing the incidence of LBW based on an analysis of the influence of the determinants of the cause. Method: observational study with cohort design. The population is all pregnant and giving birth women in East Lombok Regency amounting to 27,463 people. The sample was calculated using the binomial formula, using the simple random sampling technique, and obtained 400 samples (α = 0.05). Results Spontaneous delivery, delivery at the polindes, and delivery assisted by a midwife, while newborns are female and weigh more than 2,500 grams. The determinant effect of the mother on the incidence of low birth weight babies (LBW) consists of the age of the mother with a significance value of 0.005 RR: 1,544 (1,026 to 2,497), gestational age 0,010 RR: 1,406 (1,058 to 2,159), frequency of antenatal care (ANC) 0,005 RR: 1,763 (1,186 to 2,620). The prediction model for LBW incidence was obtained by simultaneously testing the determinants of the causes of LBW incidence in East Lombok District, namely Antenatal Care (ANC) with PR: 2,381, 95% CI (1,387 to 4,088) and a significance of 0.002. Recommendation: health promotion is carried out by taking into account the characteristics of the mother so that it is easy to understand, the team of officers will follow up on the services provided such as providing supplements, blood pressure, healthy diet and adequate family involvement.